2000
DOI: 10.1103/physrevb.61.r3808
|View full text |Cite
|
Sign up to set email alerts
|

c-axis superfluid response and pseudogap in high-Tcsuperconductors

Abstract: To gain insight into the out-of-plane electrodynamics of high-T c superconductors we have measured the absolute values and temperature dependence of the c-axis magnetic penetration depth c (T) for two typical single-layer high-T c cuprates, La 2Ϫx Sr x CuO 4 and HgBa 2 CuO 4ϩx , as a function of doping. A distinct change in the behavior of c is observed near 0.20 holes/Cu, which is related to the opening of the normal-state pseudogap. The variation of c with doping is qualitatively similar to that of the in-pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…The overall temperature dependence of z A (T ) remarkably resembles that of the c-axis superfluid density measured by Josephson plasma resonance in Bi2212 [18], penetration depth in YBCO [19], and ac susceptibility in LSCO [20]. A possible explanation is that the interlayer tunneling matrix element is enhanced near the (π, 0) point [21] such that the low-temperature QP weight near (π, 0) contributes substantially to the c-axis superfluid density.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The overall temperature dependence of z A (T ) remarkably resembles that of the c-axis superfluid density measured by Josephson plasma resonance in Bi2212 [18], penetration depth in YBCO [19], and ac susceptibility in LSCO [20]. A possible explanation is that the interlayer tunneling matrix element is enhanced near the (π, 0) point [21] such that the low-temperature QP weight near (π, 0) contributes substantially to the c-axis superfluid density.…”
mentioning
confidence: 66%
“…4(b) we compare the T -dependence of z A (T )/z A (0) between an underdoped and an overdoped sample. The coherent weight drops faster in the overdoped sample at low temperatures, once again reminiscent of the c-axis superfluid density in overdoped LSCO and the trend that the c-axis superfluid density is depleted faster upon heating as doping is increased [20].…”
mentioning
confidence: 95%
“…In addition, recent penetration depth measurements in LSCO and HgBa 2 CuO 4ϩ␦ showed that the c-axis penetration depth c Ϫ2 (0) exhibits similar behavior. 15 The apparent competition between quasistatic magnetic correlations and superconductivity thus results in a crossover to weak superconductivity characterized by a strong suppression of the superfluid density. This suppression in the underdoped region can also be directly linked to the strong reduction in entropy and condensation energy associated with the pseudogap.…”
mentioning
confidence: 99%
“…12,15,19 In total, 16 samples were investigated for each doping content. We note that grain agglomerates can be a cause of poor alignment, and to eliminate these, powders were ball milled in ethanol and dried after adding a defloculant.…”
mentioning
confidence: 99%
“…For instance La 2 CuO 4 can be doped either by alkaline earth ions or oxygen to exhibit superconductivity. The empirical phase diagram of La 2-x Sr x CuO 4 [3][4][5][6][7][8][9][10][11], depicted in …”
mentioning
confidence: 99%